2013
DOI: 10.1177/0021998313476325
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of fiber-reinforced composites and direct structural composite recycling concept

Abstract: Fiber-reinforced polymer composites are engineered materials commonly used for many structural applications because of the high strength-to-weight and stiffness-to-weight ratios. Although the service life of these materials in various applications is usually between 15 and 20 years, these often keep the physical properties beyond this time. Recycling composites using chemical, mechanical, and thermal processing is reviewed in this article. In this review of carbon, aramide, and glass fiber composites, we provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
150
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(171 citation statements)
references
References 19 publications
0
150
0
1
Order By: Relevance
“…In their comprehensive review of composite recycling processes, Asmatulu et al [71] summarized very limited available information on the energy consumption to 0.1-0.5 MJ/kg for grinding and 10-40 MJ/kg for a whole pyrolysis process. Furthermore they assessed structural recycling and concluded that such a way would be beneficial compared to the recycling of composites constituents only as it results in degraded fibres.…”
Section: Other Cfrp Recycling Methods In Lcamentioning
confidence: 99%
See 1 more Smart Citation
“…In their comprehensive review of composite recycling processes, Asmatulu et al [71] summarized very limited available information on the energy consumption to 0.1-0.5 MJ/kg for grinding and 10-40 MJ/kg for a whole pyrolysis process. Furthermore they assessed structural recycling and concluded that such a way would be beneficial compared to the recycling of composites constituents only as it results in degraded fibres.…”
Section: Other Cfrp Recycling Methods In Lcamentioning
confidence: 99%
“…It must be distinguished between production waste (dry fibres or prepreg from cutting and trimming) and EOL waste (cured composites). Several recycling routes for carbon fibres from CFRP EOL waste are under investigation and already industrially available on a small scale ( Figure 5) [70,71]. For currently discussed recycling processes, the general quality of the recycled carbon fibres (rCF) is lower compared to virgin carbon fibres (vCF).…”
Section: Recycled Carbon Fibresmentioning
confidence: 99%
“…The tensile strength of the new thermoplastic composites reinforced by recycled fibres is slightly greater (25 MPa) than the virgin fibre composites (24 MPa). The modulus of elasticity of the new generation of composites reinforced by recycled fibre is slightly lower than virgin fibre composites by 5% (Asmatulu et al, 2014). Bernasconi et al (2007) investigated the effects of mechanical recycling on the tensile strength of an injection moulded polyamide reinforced glass fibres composite.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing environmental pressure to ban or limit the disposal of waste composites via land fill-in, and instead to recycle the material [2,3]. Various processes are used for recycling thermoset matrix composites reinforced with glass fibres, including mechanical grinding, addition to cement kilns, and chemical or thermal recycling [4]. Mechanical grinding of waste composite into powder to granular sized particles (between 0.1 and 20 mm) for use as a filler material is a popular method, although the fibre cannot be recovered for reuse.…”
Section: Introductionmentioning
confidence: 99%